FORMATION OF COMPETENCIES IN TEACHERS AND STUDENTS THROUGH AN INNOVATIVE APPROACH - Abduvokhidov H. A. (Web of Journals Publishing, 2025)
Changes in all directions in life are often determined by innovative processes.Even the phrases used in the education system of the former are becoming obsolete and replaced by new terms.While students have been focused on learning to write only reading in schools, to this day, innovative technologies of education are entering the education system due to progress.The main purpose of the cross section of all branches operating in the educational system, for the faster development of education,innovation is the faster introduction of educational elements into the system, but for this, first of all, the team of educators in secondary schools should be prepared in every possible way. Today, in our country,it is necessary to pay great attention to the training of mature, physically strong, competent, independent-minded, strong-willed and enterprising personnel in every possible way, first of all, through the improvement of the educational system.Any innovation will not be easily introduced into life, it will have its own complexity and difficulties, the concepts of"innovation","innovation processes", "innovation education", "innovation technologies"will first of all have to be thoroughly studied from a modern point of view. Since the creation of the universe,development and progress have been the main part of human activity.As a person's experience in life increases, he increases his mental capabilities by improving his activities in every field, in a constant state he himself develops. Development is a concept inherent in a person. This also applies to pedagogical activity. To upbringing,the ground is initially laid in the family, the foundation is laid. In the educational system, the student is given both upbringing and education. In order to formulate the technological competence of students on the basis of an innovative approach, first of all, the teacher must have a general understanding of pedagogical innovations.